Perbandingan Pendidikan Kesehatan antara Metode Diskusi dan Pemecahan Masalah dalam Perubahan Perilaku Pasien Diabetes Melitus Tipe 2 Di RSUD Swadana Pekalongan - Sunaryo,; Haryati, Welas (Jurusan Keperawatan FIKES UNSOED, 2007)
Forty-five percents of 2.4 millions diabetes mellitus patients in Indonesia could not be treated well because of noncompliance to the treatment. One of the reasons of this noncompliance was the lack of understanding about diabetes mellitus disease. The problem of this research was: Ã¢â‚¬Å“Is there any difference between discussion and problem solving method of health education for changing the attitude of patients with diabetes mellitus type-2 in RSUD Swadana PekalonganÃ¢â‚¬Â. The aim of this research was to compare between discussion and problem solving method of health education for changing the attitude of patients with diabetes mellitus type-2 in RSUD Swadana Pekalongan. It was Quasi Experimental Research with Non Equivalent Control Group Design with Pre-test and Post-test. The Subject of this research was out-patient with diabetes mellitus type-2 in RSUD Swadana Pekalongan, who were matched with the inclusion criteria as many as 124 persons. The research sample was fixed with proposional random sampling technique. The sample of discussion group was consisted of 23 persons and problem solving group consisted of 24 persons. The measurement tool in pre and post-tes for knowledge was criteria referenced test, in questionnaire form, with validity of 0,3367 Ã¢â‚¬â€œ 0,9002 and reliability of 0,8655. The measurement tool for attitude was attitude scale questionnaire of Likert with validity of 0,3027 Ã¢â‚¬â€œ 0,7426 and reliability of 0,8678. Enzymatic method (glucose oxidation and hexokinase) was measurement tool for glucose bloodÃ¢â‚¬â„¢s level. Statistic test used Chi-Square and student t-test with significance level p = 0,05. The result of this research showed that problem solving method could more improve the rate of knowledgeÃ¢â‚¬â„¢s mark (p0,05) for improving the rate of attitude mark and the rate of unload blood glucose level in out-patients with diabetes mellitus type-2 in RSUD Swadana Pekalongan.